Evaluation of the introduction of the OSCE to the fifth‐year Geriatric Medicine Teaching Programme. (19th September 2016) - Vanlint, Andrew; Tam, Khai Loon; Yu, Solomon; Visvanathan, Renuka
Abstract : Aim: An Observed Structured Clinical Examination (OSCE) was integrated into the assessment for senior medical students undertaking a 4.5‐week geriatric medicine teaching block at one campus. The feasibility and acceptability of an OSCE were examined. Methods: Students completed eight questions regarding the OSCE using a 6‐point Likert scale and two additional questions, using free text, highlighting the strengths and potential areas for improvement. Changes were made every 6 months over a two‐year period in response to student evaluation. Results: Improvements included adjusting the format to conform with end‐of‐year examinations and introducing simulated patients. Following these improvements, students perceived improved structure and sequence to the assessments, improved opportunity for demonstration of skills and knowledge and that the assessment was fair. Conclusion: This preliminary research provides evidence that it is feasible to introduce OSCE as a form of assessment into a geriatric medicine teaching programme and student evaluation can be used to inform improvements.